2014
DOI: 10.5811/westjem.2014.3.19658
|View full text |Cite
|
Sign up to set email alerts
|

Typed versus Voice Recognition for Data Entry in an Electronic Health Record: Emergency Department Physician Time Utilization and Interruptions

Abstract: IntroductionUse of electronic health record (EHR) systems can place a considerable data entry burden upon the emergency department (ED) physician. Voice recognition data entry has been proposed as one mechanism to mitigate some of this burden; however, no reports are available specifically comparing emergency physician (EP) time use or number of interruptions between typed and voice recognition data entry-based EHRs. We designed this study to compare physician time use and interruptions between an EHR system u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…One of the main complaints about EPD adoption is the increase in charting time. 20 Providers may be spending more time after clinical shifts to chart; this was not accurately captured in our metrics. We had attempted to compare subjective reported provider charting times after shifts, but the data were incomplete and could not be adequately analyzed.…”
Section: Limitations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main complaints about EPD adoption is the increase in charting time. 20 Providers may be spending more time after clinical shifts to chart; this was not accurately captured in our metrics. We had attempted to compare subjective reported provider charting times after shifts, but the data were incomplete and could not be adequately analyzed.…”
Section: Limitations and Discussionmentioning
confidence: 99%
“…The act of dictation may prevent provider interruptions in the ED and may not necessarily increase charting time. 20 Voice recognition profiles do require additional training and curation to improve accuracy and are cheaper than transcriptionist but more expensive than typing. 21 The advantage of the voice recognition program spelling correctly is offset by the need to proofread the dictated text, but accuracy has been shown to nearly as good as human transcription.…”
Section: Limitations and Discussionmentioning
confidence: 99%
“…In a direct comparison of voice recognition software and transcription services, one group found voice recognition to be superior given the shorter turnaround time and decreased transcription costs [22]. Another study found a decreased number of physician interruptions when voice recognition software was used in place of traditional typing-based charting [23].…”
Section: Reviewmentioning
confidence: 99%
“…Cost-effectiveness of SRS over traditional transcription has also been noted [ 9 ]. Fewer interruptions of emergency room physicians occurred with SRS when compared to written data entry [ 10 ].…”
Section: Introductionmentioning
confidence: 99%